Values-Based Education for Sustainability Marketers: Two Approaches for Enhancing Student Social Consciousness. (April 2015) - Markley Rountree, Melissa; Koernig, Stephen K.
Sustainable development has been a hot button issue for decades, and yet business schools continue to struggle with accessible, meaningful and effective strategies to incorporate the topic into their curricula. To extend the teaching toolbox of educators, we describe two complementary marketing courses that use values-based learning to incorporate a sustainability focus in conjunction with traditional marketing topics. Using nonprofit organizations as the foundation, experiential learning methods are presented that can facilitate development of the moral, ethical, and perceptual foundation graduates need to be successful in today's sustainability focused marketplace. Specific objectives and measures related to building this foundation also are described. Preliminary results are presented suggesting that this two-pronged focus is very effective at increasing and maintaining interest in sustainability issues, as well as increasing the number of marketing students and graduates working in sustainability marketing positions.